A research on the reviews of the social science teachers who serve in Turkey and Germany about chaotic situations they encounter in class - Karadeniz, Oğuzhan; Er, Harun; Turan, Selçuk (Springer editorial@springerplus.com, 2016)
Today’s world has a consistently dynamic structure in constant change and development. We live in a world where we can encounter positive and negative unexpected situations and everything can happen every moment. That such environments in which people and communities live change constantly and quickly shows that people live in a chaos laden environment. The social science lesson which has a very important function in terms of adapting to social life and socializing has an important part in the education of individuals. Thus, the teachers who give lessons regarding the lesson which holds such importance state chaotic situations they encounter in the teaching-instruction process and the evaluation of their responses consists the core of our study. In this study, the aim is the comparative evaluation of the chaotic situations which social science (history, geography, politics, citizenship education) teachers, who serve in Turkey and Germany, encounter in the course. The study using qualitative research methods was carried out by a total of 20 social sciences teachers including 10 in Turkey and 10 in Germany working in 5 different locations (history-geography, politics, citizenship education). As a result of the study, the chaotic situations that teachers who serve in Turkey and Germany, encounter are different in specific ways but basically similar. While teachers in Germany pointed out student-centered problems, the teachers in Turkey tended to non- students factors mostly. © 2019 Elsevier B.V., All rights reserved.
Keywords: Chaos; Lesson; Social Studies; The Chaotic Situation